Changing hands: persistent alterations to body image following brief exposure to multisensory distortions - Perera, Andrea Treshi-Marie; Newport, Roger; McKenzie, Kirsten J. (Springer, 2017)
The dynamic flexibility of body representation has been highlighted through numerous lines of research that range from clinical studies reporting disorders of body ownership, to experimentally induced somatic illusions that have provided evidence for the embodiment of manipulated representations and even fake limbs. While most studies have reported that enlargement of body parts alters somatic perception, and that these can be more readily embodied, shrunken body parts have not been found to consistently alter somatic experiences, perhaps due to reduced feelings of ownership over smaller body parts. Over two experiments, we aimed to investigate the mechanisms responsible for altered somatic representations following exposure to both enlarged and shrunken body parts. Participants were given the impression that their hand and index finger were either longer or shorter than veridical length and asked to judge veridical finger length using online and offline size estimation tasks, as well as to report the degree of ownership towards the distorted finger and hand representations. Ownership was claimed over all distorted representations of the hand and finger and no differences were seen across ownership ratings, while the online and offline measurements of perceived size demonstrated differing response patterns. These findings suggest that ownership towards manipulated body representations is more bidirectional than previously thought and also suggest differences in perceived body representation with respect to the method of measurement suggesting that online and offline tasks may tap into different aspects of body representation.